An Exploration of EFL Teachers’ Perceptions and Experiences of E-Learning Implementation through the Concern-Based Adoption Model - Desy Rusmawaty; Istanti Hermagustiana; Sunardi Sunardi (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2023)
Concerns-Based Adoption Model (CBAM) is a framework that can be used to guide the implementation of e-learning in educational contexts. CBAM focuses on the problems individuals have during the implementation process and helps to discover solutions to these difficulties. The objective of this study was to get an overview of EFL teachers' perspectives and practices about implementing e-learning based on the CBAM. The CBAM was employed as a model to grasp the challenges and levels of e-learning adoption among English as Foreign Language (EFL) teachers. For this study, ten EFL teachers who knew how to use e-learning participated in semi-structured interviews to provide qualitative data. The interview transcripts were subjected using the thematic analysis. According to the results of this research, some EFL teachers were early adopters of e-learning, but others have shown considerable rejection. Among the teachers' objections were technical obstacles, a lack of training, and skepticism over the effectiveness of e-learning in increasing students' language skills. The study also revealed that the CBAM was an excellent tool for identifying the issues and degrees of e-learning usage among EFL teachers. The model offers a framework for describing the stages of e-learning adoption, from awareness to regular use, and strategies to assist teachers in their adoption process. This study expands our knowledge of the opinions and experiences of EFL teachers towards implementing e-learning. The findings indicate the need to provide teachers with workshops and training to increase their usage of e-learning and enhance the efficacy of EFL teaching instruction.